The crisis of race in higher education : a day of discovery and dialogue - Tate, William F.; Staudt, Nancy; Macrander, Ashley (Bingley : Emerald Group Publishing Limited, 2016)
The compendium of writings in this edited volume sheds light on the event'Race & Ethnicity: A Day of Discovery and Dialogue' at Washington University in St. Louis and the work current students, faculty, and staff are doing to improve inclusivity on campus and in St. Louis. The book includes speeches, reflections, art, and photography aligned with the Day of Discovery and Dialogue in addition to original academic work on race in higher education, race in St. Louis, and race in the United States. Leading scholars and emerging voices feature in this volume, filling a void in the race and higher education literature since it will foreground a case study of a single university at the epicenter of a national racial crisis and how a university-wide event brought a campus together. This praxis focus may have far reaching impact in aiding other universities across the country in addressing racial tensions in their own communities.
Prelims -- Section 1: the social construction of race and ethnicity -- Genetics and the origins of race -- The missing box: multiracial student identity development at a predominantly white institution -- Narrating race and identities from the periphery: diversity, dilemma, and discourses -- Section 2: race and ethnicity in everyday life -- Retaining students of color in higher education: expanding our focus to psychosocial adjustment and mental health -- Roadblocks on the way to higher education: non-dominant cultural capital, race, and the'schools are equalizer' myth -- Learning to live together: connecting the classroom to the community for racial justice in housing -- Academic and community partnerships and social change -- Section 3: moving beyond stereotypes -- On the light versus dark side of empathy: implications for intergroup dynamics in a diverse society -- Storytelling in higher education -- The roots are racism: historical and current racial bias on college campuses and their (unintended) push on the diversity agenda -- Bringing ourselves back from extinction in academia: becoming an Indigenous scholar -- A future of native students: from victimization to value to victory -- Section 4: the future and our university community -- The chancellors graduate fellowship program: a pre- and post-grutter analysis -- Doing diversity in higher education for international students -- The john b. ervin scholars programs'legacy of commitment': grounded in discovery and dialogue -- Honoring our investment: low-income student success at washington university in st. louis -- Academic support for an increasingly diverse undergraduate population: challenges in initiative design and implementation -- A private university called to a public mission: selective higher education, diversity, and access -- Afterwordthe crisis of race in higher education: a focus on inclusion -- About the artists -- About the authors.
Includes bibliographical references.
Print version record
Keywords: Education: adult & continuing education; Universities; Minorities -- Education -- United States; Discrimination in education -- United States; Multicultural education -- United States